AN ANALYSIS OF DAVID AND EMILY CALLAWAY’S PSYCHOPATH PROBLEMS IN HIDE AND SEEK MOVIE VIEWED FROM SIGMUND FREUD’S PSYCHOANALYSIS THEORY - dean rahmat fuady; suhendar suhendar (Journal of English Language and Literature (JELL), 2019)
This research aims to analyze the main characters in Hide and Seek movie as the characters who have psychopathic problem and Dissociative Identity Disorder. In relation to which, the writer studied Hide and Seek movie as the unit of analysis. Psychopathic problems viewed from Sigmund Freud’s psychoanalysis concepts are used for the review of related literature theories or concepts of the research. Therefore, the method of the research is descriptive qualitative, which tries to explain about the intrinsic elements of the movie; such as characterization and the scenes of the movie, then followed by analyzing them through Sigmund Freud’s psychoanalysis. Through observations of the scenes and the behavior of the main characters the writer reveals David and Emily have been identified to have psychopathic characters such as manipulative, parasitical, deceitful, power hungry, less empathy, often lie, shallow affect and poor behavioral control. In addition, the causes of such character are trauma and stress viewed from Sigmund Freud’s psychoanalysis theory